PENGARUH NILAI NASABAH TERHADAP LOYALITAS MELALUI KEPUTUSAN NASABAH SEBAGAI VARIABEL INTERVENING PADA PT PERMODALAN NASIONAL MADANI (PNM) MEKAR CABANG HAMPARAN PERAK - Mona Lisa; Ahmad Fadli; Emma Novirsari (Jurnal Mahkota Bisnis (Makbis), 2022)
Abstract This study aims to determine whether customer value and customer loyalty affect customer satisfaction at PT. Madani National Capital (PNM) Mekaar Branch Overlay Perak. This type of research is quantitative research. This research was conducted at the office of PNM Mekar (Building a Prosperous Family Economy) which is located at Jl. Sukaramai Hamlet III Pasar II No. 169 Kec. Deli Serdang Regency Silver Expanse. The population in this study consisted of all customers of PNM Mekar Branch Hamparan Perak, amounting to 4393 customers. The number of samples in this study were 500 PNM Mekaar Hamparan Perak customers. The results of this study There is a partial influence between customer value on customer loyalty at PT. PNM Mekaar Perak Branch. There is a partial influence between customer loyalty on customer satisfaction at PT. PNm Mekaar Perak Branch. There is a partial influence between customer satisfaction and customer value at PT. PNM Mekaar Branch Hamparan Perak. Customer value and customer loyalty simultaneously affect customer satisfaction at PT. PNM Mekaar Perak Branch